Santos Rego, M.A., Lorenzo, M. y Vázquez. A. (2018). Educación no formal y empleabilidad de la juventud. Madrid: Síntesis. ISBN: 978-84-9171-094-3 - Arizmendi Domínguez, Aitor (Journal of Supranational Policies of Education (JOSPOE), 2018)
Santos Rego, M.A., Lorenzo, M. y Vázquez. A. (2018). Educación no formal y empleabilidad de la juventud. Madrid: Síntesis. ISBN: 978-84-9171-094-3